Pengembangan e-Book Menggunakan Aplikasi Flip Pdf Corporate Edition Pada Mata Pelajaran Bimbingan TIK Kelas VII SMP - Reanda Ramadhan Yudianto; Eldarni Eldarni (Jurnal Family Education, 2023)
This development research aims to produce e-book-based teaching materials on ICT guidance subjects for class VII junior high school. The development of e-book-based media using the Flip PDF Corporate Edition application seeks to help the learning process for students to be more interesting and enjoyable and can be used anytime and anywhere. This research stems from the results of interviews from educators who need media or media variations in supporting students to learn at SMP Negeri 25 Padang. The development that researchers do uses the 4D development model. The stages of research using this 4D model are Define, Design, Development, and Dissemination. The instruments used are interviews, documentation and assessment sheets (questionnaires). The results of the research conducted explained that the research from the media validator was "Very Feasible" with an average obtained of 4.86 and a percentage of 97.35%. The assessment of the material validator was declared "Very Suitable" with an average score obtained of 4.78 and a percentage of 95.7%. While the practicality assessment from students was declared "Very Practical" with an average obtained of 66.95 from the maximum average score of 70 and a percentage obtained of 95.64% with 21 students as respondents. Based on these calculations, the conclusion of the e-book-based learning media in class VII ICT guidance subjects developed is "Very Practical" to be used in the learning process. So it can be concluded that the validity test and practicality test can be concluded that this e-book is suitable for use.